An additional editing site is present in apolipoprotein B mRNA. - Navaratnam, N (1991)
Human intestinal apolipoprotein (apo) B mRNA undergoes a C to U RNA editing at nucleotide 6666 to generate a translation stop at codon 2153, which defines the carboxy-terminal of apo B48. Here we show that two of eleven human intestinal cDNAs spanning residue 6666 were edited from a genomically-encoded C to a T at residue 6802 as well as at residue 6666. This additional editing converts Thr (ACA) codon 2198 to Ile (AUA). Synthetic RNA including the nucleotide 6802 was edited in vitro by intestinal extracts at 10-15% of the editing efficiency of nucleotide 6666. A sequence is identified as important for recognition by the editing activity. No secondary structural homology was identified between the two edited sites. No other sequence in the region between 6411 and 6893 nucleotides of apo B mRNA was found to be edited in vivo or in vitro. Apo B RNA editing extracts from intestine did not edit maize cytochrome oxidase II mRNA.